Apparent digestibility and performance of West African dwarf sheep fed ensiled maize stover and concentrate supplements - Amuda, A. J.; Okunlola, D. O. (Nigerian Journal of Animal Science, 2023)
A feeding trial was conducted on 20 growing West African Dwarf (WAD) sheep to determine the dietary effect of ensiled maize stover (EMS) and concentrate supplements (CS). Individual feed intake and weight changes were determined for 105 days to allow measurement of the effects of the feeds on weight gain, feed intake, apparent digestibility and feed conversion ratio (FCR) of West African dwarf sheep. The animals were randomly allocated to five experimental diets: A (100% EMS), B (75% EMS + 25% CS), C (50% EMS + 50% CS), D (25% EMS + 75% CS) and E (100% CS). Significant differences (P < 0.05) occurred in body weight gain (BWG), dry matter intake (DMI), metabolic weight gain (MBW), metabolic daily dry matter intake (MDDMI) and feed conversion ratio (FCR) among the treatments means. Animals on diet E (100% CS) had the highest weight gain (90.48g/d/head) and FCR (6.55). However, BWG of animals on diet A (silage alone) was negative (-12.70g/d/head), indicating that the animals lost weight. DMI decreased significantly with increased inclusion of maize stover silage. Significant differences occurred among the treatments for organic matter digestibility, cellulose, hemicellulose and metabolisable energy while other parameters like digestible crude protein, digestible crude fibre, nitrogen free extract and fibre fractions were similar across the dietary treatments. The results suggest that maize stover silage could be utilized to supply energy requirements of sheep and improved nutrient digestibility and dry matter intake when fed with concentrate supplements.